High-ultraviolet-rejection-rate, high-hardness and high-hydrophobicity coating and preparation method thereof

By using resins such as polyurethane acrylate, epoxy acrylate and other resins combined with specific additives on the glass screen of electronic products, a high ultraviolet barrier rate, high hardness, and high hydrophobic coating was prepared, which solved the hardness of the existing coating. The shortcomings in barrier and hydrophobic properties achieve higher performance and environmental protection.

CN119490785AActive Publication Date: 2025-02-21JIANGXI MEIJI NEW MATERIAL TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510068439.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-02-21
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The existing ultraviolet cured coatings in terms of hardness, ultraviolet barrier, hydrophobic properties and environmental protection cannot meet the high standards of electronic products surfaces.

Method used

Polyurethane acrylate, epoxy acrylate, amino resin and other resins are used as curing substrates, combined with UV monomers, photoinitiators, ultraviolet absorbers and crosslinking additives, and high ultraviolet barrier rates are prepared through specific ratios and treatment methods. Highly hard and hydrophobic coating.

Benefits of technology

It has achieved the improvement of high UV barrier rate, hardness and hydrophobic performance, and has environmentally friendly characteristics, which are suitable for the surface treatment of glass screens of electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490785A_ABST
    Figure CN119490785A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, and provides a high-ultraviolet-rejection-rate, high-hardness and high-hydrophobicity coating and a preparation method thereof.The coating is prepared from, by mass, urethane acrylate, epoxy acrylate, amino resin, a UV monomer, a photoinitiator, an ultraviolet light absorber and a crosslinking auxiliary. The preparation method of the coating comprises the following steps: putting the polyurethane acrylate, the epoxy acrylate, the amino resin, the UV monomer and the photoinitiator into a container, and mixing and stirring to obtain a uniformly mixed mixture; then adding an ultraviolet light absorber and a cross-linking auxiliary agent, and mixing and stirring to obtain the high-ultraviolet-rejection-rate, high-hardness and high-hydrophobicity coating. The coating is coated on the surface of a base material by using an ink regulating knife, a layer of release film is covered, uniform rolling is performed, ultraviolet irradiation is performed, then the release film is uncovered, and the base material is placed in a constant-temperature oven to be baked, so that the coating is obtained. The coating has the advantages of high hydrophobicity, high hardness and high ultraviolet rejection rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a coating with high ultraviolet blocking rate, high hardness and high hydrophobicity and a preparation method thereof. Background Art

[0002] The display screens of modern electronic products are generally made of specially treated glass or plastic. Glass is favored for its excellent hardness and scratch resistance and is widely used in a variety of electronic devices such as smartphones, tablets, and computer monitors. The scratch resistance of glass mainly depends on its hardness. High-hardness glass can withstand the wear and scratches in daily use. However, the glass surface easily absorbs water droplets and fingerprints, causing the surface to become dirty. In order to improve the scratch resistance and anti-pollution ability of the screen, and at the same time obtain the effect of blocking ultraviolet rays to protect the eyes, the glass screen is usually covered with one or more layers of protective materials, such as chemically strengthened glass, surface hardened anti-fouling coating, and ultraviolet blocking coating. With the market's increasing requirements for the performance of UV-cured coatings, the existing UV-cured coatings in terms of hardness, UV blocking, hydrophobicity and environmental protection have gradually failed to meet the high standards for surface coating treatment of electronic products.

[0003] A Chinese invention patent with patent publication number CN115403969A discloses a UV-cured highly wear-resistant and highly hydrophobic coating and a preparation method thereof. In this disclosure, a modification method of introducing fluorine atoms and silicon atoms into the resin matrix is ​​adopted to solve the problem of poor surface hardness and wear resistance of the photocured coating in the prior art. However, the coating used in its solution contains solvent-based UV resin and organic solvent, which limits the actual application scope of the coating. In addition, the UV coating in this patent does not have a UV blocking effect.

[0004] A Chinese invention patent with patent publication number CN1958698A discloses a thermosetting water-based UV blocking coating and a coating film obtained therefrom. In this disclosure, a water-based polyurethane resin is mixed with a UV absorber to prepare a coating having the ability to block UV rays below 380nm. However, the coating obtained by this scheme is not hydrophobic and is easily damaged by friction during use.

[0005] Therefore, the development of a coating with high UV blocking rate, high hardness and high hydrophobicity has obvious application value in the field of surface treatment of glass screens of electronic products. Summary of the invention

[0006] In view of the deficiencies of the prior art, the object of the present invention is to provide a coating with high ultraviolet blocking rate, high hardness and high hydrophobicity and a preparation method thereof.

[0007] The present invention first provides a coating with high UV blocking rate, high hardness and high hydrophobicity, which comprises the following components by weight: Polyurethane acrylate 20% to 35%; Epoxy acrylate 20% to 35%; Amino resin 20% to 35%; UV monomer 5%~15%; Photoinitiator 1% to 5%; Ultraviolet absorber 1% to 10%; Cross-linking agent 1%~10%.

[0008] Furthermore, the mass ratio of urethane acrylate, epoxy acrylate, amino resin, and ultraviolet absorber is preferably 25%:28%:26%:5%.

[0009] Furthermore, the mass ratio of UV monomer, photoinitiator and cross-linking aid is preferably 10%:1%:5%.

[0010] Furthermore, the polyurethane acrylate is at least one of silicone-modified polyurethane acrylate, organic fluorine-modified polyurethane acrylate, and fluorine-silicon-modified polyurethane acrylate; the epoxy acrylate is at least one of modified epoxy acrylate, bisphenol A epoxy acrylate, and novolac epoxy acrylate; the amino resin is at least one of hexamethoxymethyl melamine resin, high-iminomethyl etherified amino resin, and butyl etherified amino resin; and the ultraviolet absorber is at least one of benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, and triazine-based ultraviolet absorbers.

[0011] Furthermore, the UV monomer is at least one of tris(2-hydroxyethyl)isocyanurate triacrylate, isobornyl methacrylate, and hydroxyethyl methacrylate; the photoinitiator is at least one of 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; and the crosslinking aid is at least one of titanate, alkenyl silane coupling agent, and aminosilane coupling agent.

[0012] Furthermore, the polyurethane acrylate is preferably fluorosilicone-modified polyurethane acrylate; the epoxy acrylate is preferably modified epoxy acrylate; the amino resin is preferably hexamethoxymethyl melamine resin; and the ultraviolet absorber is preferably a triazine ultraviolet absorber.

[0013] Furthermore, the UV monomer is preferably hydroxyethyl methacrylate; the photoinitiator is preferably 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; and the crosslinking aid is preferably an aminosilane coupling agent.

[0014] Furthermore, the mass ratio of 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide to phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide is 8:2.

[0015] The present invention also provides a method for preparing the above-mentioned high ultraviolet blocking rate, high hardness and high hydrophobicity coating, comprising the following steps: (1) Place polyurethane acrylate, epoxy acrylate, amino resin, UV monomer, and photoinitiator in a container, and mix and stir for 60 to 90 minutes to obtain a uniform mixture; (2) adding an ultraviolet absorber and a crosslinking aid to the mixture of step (1), mixing and stirring for 30 to 60 minutes to obtain a coating with high ultraviolet blocking rate, high hardness and high hydrophobicity; (3) Apply the coating of step (2) to the surface of the substrate with an ink knife, cover it with a layer of release film, roll it evenly, irradiate it with ultraviolet light, then remove the release film, and bake the substrate in a constant temperature oven at 150° C. for 30 min to 50 min to obtain a coating with high ultraviolet blocking rate, high hardness and high hydrophobicity.

[0016] Furthermore, in step (3), the substrate is at least one of 1 mm tempered glass, 3 mm tempered glass, 1 mm ultra-clear glass, and 3 mm ultra-clear glass; the release film is a high temperature resistant PET release film; the wet film thickness of the coating after rolling is uniformly formed is 10 um to 20 um; the ultraviolet light source is a 395 nm-UV LED light source, and the amount of ultraviolet light is 1500 mJ / cm 2 ~2000mJ / cm 2 .

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. Strong hydrophobicity. Fluorosilicone modified polyurethane acrylate, modified epoxy acrylate and hexamethoxymethyl melamine resin are used as the curing matrix. The three resins react to form a network cross-linking, which improves the hardness of the coating and has high hydrophobicity.

[0018] 2. Good wear resistance. Hydroxyethyl methacrylate is used as a diluent monomer, aminosilane coupling agent is used as a crosslinking aid, 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide are used as photoinitiators to increase the double bond conversion rate of the resin as a curing matrix, further improving the hardness and wear resistance of the coating.

[0019] 3. High UV blocking rate. The use of triazine-based UV absorbers enables the coating to have a high UV blocking rate of less than 380nm. When the coating thickness is 10um, the UV blocking rate of less than 380nm reaches more than 90%.

[0020] 4. During curing, the film is irradiated with a UVLED lamp with a specific wavelength of 395nm and thermal curing is used to avoid the failure of the UV blocker due to the reaction after UVLED lamp irradiation, and solve the problem that UV absorbers are difficult to apply to UV-curing coatings.

[0021] 5. Using specific types of fluorosilicone modified polyurethane acrylate, modified epoxy acrylate, and hexamethoxymethyl melamine resin as the curing matrix, the coating is prepared by laminating, irradiating a UVLED lamp with a specific wavelength, and thermally curing. The coating has a high blocking rate for ultraviolet rays below 380nm, a pencil hardness of 5H, and excellent hydrophobicity, and has obvious application value in the field of surface treatment of glass screens of electronic products. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the specific implementation of the present invention or the technical solution in the prior art, the drawings required for describing the specific implementation or the prior art will be briefly introduced below. Obviously, the drawings described below are only one implementation of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 This is a diagram of the hydrophobicity test results of Example 1.

[0024] Figure 2 This is a diagram of the hydrophobicity test results of Example 2.

[0025] Figure 3 This is a diagram of the hydrophobicity test results of Example 3.

[0026] Figure 4 This is a diagram of the hydrophobicity test results of Example 4.

[0027] Figure 5 This is a diagram of the hydrophobicity test results of Example 5.

[0028] Figure 6 This is a diagram of the hydrophobicity test results of Example 6.

[0029] Figure 7 This is a diagram of the hydrophobicity test results of Example 8.

[0030] Figure 8 This is a diagram of the hydrophobicity test results of Example 9.

[0031] Fig. 9 This is a diagram of the hydrophobicity test results of Example 10.

[0032] Fig.10 This is a diagram of the hydrophobicity test results of Example 11.

[0033] Fig.11 This is a diagram of the hydrophobicity test results of Example 12.

[0034] Fig.12 This is a diagram of the hydrophobicity test results of Example 13.

[0035] Fig.13 This is a graph showing the hydrophobicity test results of Example 15.

[0036] Fig.14 This is a graph showing the hydrophobicity test results of Example 16.

[0037] Fig.15 This is a graph showing the hydrophobicity test results of Example 17.

[0038] Fig.16 This is a graph showing the hydrophobicity test results of Example 18.

[0039] Fig.17 This is a graph showing the hydrophobicity test results of Example 19.

[0040] Fig.18 This is a graph showing the hydrophobicity test results of Example 20.

[0041] Fig.19 This is a graph showing the hydrophobicity test results of Example 21.

[0042] Fig. 20 This is a graph showing the hydrophobicity test results of Example 22.

[0043] Fig.21 This is a graph showing the hydrophobicity test results of Example 23.

[0044] Fig. 22 This is a graph showing the hydrophobicity test results of Example 24.

[0045] Fig.23 This is a graph showing the hydrophobicity test results of Example 25.

[0046] Fig.24 This is a graph showing the hydrophobicity test results of Example 26. DETAILED DESCRIPTION

[0047] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the technical scheme in the specific implementation mode of the present invention is clearly and completely described below to further illustrate the present invention. Obviously, the specific implementation mode described is only a part of the implementation mode of the present invention, rather than all styles.

[0048] The high ultraviolet blocking rate, high hardness and high hydrophobicity coating of the present invention comprises the following components by weight: Polyurethane acrylate 20% to 35%; Epoxy acrylate 20% to 35%; Amino resin 20% to 35%; UV monomer 5%~15%; Photoinitiator 1% to 5%; Ultraviolet absorber 1% to 10%; Cross-linking agent 1%~10%.

[0049] The preferred mass proportion of each component is: Polyurethane acrylate 25%; Epoxy acrylate 28%; Amino resin 26%; UV monomer 10%; Photoinitiator 1%; UV absorber 5%; Cross-linking aid 5%.

[0050] Among them, in the specific selection of each component, the polyurethane acrylate is at least one of organic silicon modified polyurethane acrylate, organic fluorine modified polyurethane acrylate, and fluorine silicon modified polyurethane acrylate; the epoxy acrylate is at least one of modified epoxy acrylate, bisphenol A epoxy acrylate, and novolac epoxy acrylate; the amino resin is at least one of hexamethoxymethyl melamine resin, high iminomethyl etherified amino resin, and butyl etherified amino resin; the ultraviolet absorber is at least one of benzophenone ultraviolet absorber, benzotriazole ultraviolet absorber, and triazine ultraviolet absorber; the UV monomer is at least one of tris(2-hydroxyethyl)isocyanuric acid triacrylate, isobornyl methacrylate, and hydroxyethyl methacrylate; the photoinitiator is at least one of 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; the crosslinking aid is at least one of titanate, alkenyl silane coupling agent, and aminosilane coupling agent.

[0051] As a preferred embodiment, the polyurethane acrylate is fluorosilicone modified polyurethane acrylate; the epoxy acrylate is modified epoxy acrylate; the amino resin is hexamethoxymethyl melamine resin; the ultraviolet absorber is a triazine ultraviolet absorber; the UV monomer is hydroxyethyl methacrylate; the photoinitiator is 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and the mass ratio of 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide to phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide is 8:2; and the crosslinking aid is an aminosilane coupling agent.

[0052] The present invention also provides a method for preparing the above-mentioned high ultraviolet blocking rate, high hardness and high hydrophobicity coating, comprising the following steps: (1) Place polyurethane acrylate, epoxy acrylate, amino resin, UV monomer, and photoinitiator in a container, mix and stir for 60 to 90 minutes to obtain a uniform mixture; (2) adding an ultraviolet absorber and a crosslinking aid to the mixture of step (1), mixing and stirring for 30 to 60 minutes to obtain a coating with high ultraviolet blocking rate, high hardness and high hydrophobicity; (3) Apply the coating in step (2) to the surface of the substrate with an ink knife. The substrate can be 1mm tempered glass, 3mm tempered glass, 1mm ultra-white glass or 3mm ultra-white glass. Cover it with a layer of high-temperature resistant PET release film, roll it evenly, and ensure that the wet film thickness of the coating is 10um to 20um after rolling evenly. Then irradiate it with ultraviolet light. The ultraviolet light source is a 395nm-UVLED light source, and the amount of ultraviolet light irradiation is 1500mJ / cm 2 ~2000mJ / cm 2 Then, peel off the release film and place the substrate in a constant temperature oven at 150°C and bake for 30 to 50 minutes to obtain a coating with high UV blocking rate, high hardness and high hydrophobicity.

[0053] In order to determine the preferred components and suitable contents of the high UV blocking rate, high hardness and high hydrophobicity coating of the present invention, the present invention prepared a control test with different components and different contents according to the above method.

[0054] Wherein, in step (3), the substrate is 3mm tempered glass; the wet film thickness of the coating after rolling is uniform is 10um; the ultraviolet irradiation light source is 395nm-UVLED light source, and the amount of ultraviolet irradiation is 1500mJ / cm 2 .

[0055] Among them, the fluorosilicone modified polyurethane acrylate used in the experiment was purchased from Dongguan Inoue New Material Development Co., Ltd., model UV-9843-9; modified epoxy acrylate was purchased from Jining Tangyi Chemical Co., Ltd., model WDS-8056; hexamethoxymethyl melamine resin was purchased from Foshan Wengkaier Co., Ltd., model CYMEL 303; hydroxyethyl methacrylate, CAS No. 868-77-9; 2,4,6-(trimethylbenzoyl) diphenyl phosphine oxide, CAS No. 75980-60-8, phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, CAS No. 42013-20-7; triazine series ultraviolet absorber, CAS No. 147315-50-2; aminosilane coupling agent, CAS No. 2530-85-0.

[0056] All the prepared high UV blocking rate, high hardness and high hydrophobicity coatings were tested for hardness, abrasion resistance, hydrophobicity and UV blocking rate, and then compared. The test methods are: Adhesion grade test: All prepared coatings are tested for adhesion in accordance with GB / T9286-2021 "Paints and varnishes: Cross-cut test".

[0057] Hardness test: All prepared coatings are tested for hardness according to GB / T6739-2022 "Paints and varnishes: Determination of film hardness by pencil method".

[0058] Abrasion resistance test: Use American TABER CS-17 abrasion-resistant rubber to rub all prepared coatings 100 times with a weight of 1kg, and observe the surface condition of the coating. If there is no scratch on the coating surface, it is grade A; if there is a scratch on the coating surface, it is grade B.

[0059] Hydrophobicity test: All prepared coatings were tested for contact angle using a contact angle meter. The larger the contact angle, the stronger the hydrophobicity of the coating (the experimental results are shown in Figures 1 to 24 as shown).

[0060] UV blocking rate test: All prepared coatings are tested for UV blocking rate below 380nm using a UV blocking rate tester. Five points are randomly selected and the average value is taken. The greater the blocking rate, the stronger the UV blocking performance.

[0061] The comparison data is shown in the following table: Table 1 Composition and content data of Examples 1 to 7 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Silicone modified polyurethane acrylate 25 0 0 0 0 0 0 Organic fluorine modified polyurethane acrylate 0 25 0 0 0 0 0 Fluorosilicone modified polyurethane acrylate 0 0 25 15 20 30 35 Modified epoxy acrylate 28 28 28 28 28 28 28 Hexamethoxymethyl melamine resin 26 26 26 26 26 26 26 UV monomer 10 10 10 20 15 5 0 Photoinitiator 1 1 1 1 1 1 1 Triazine UV absorbers 5 5 5 5 5 5 5 Crosslinking aid 5 5 5 5 5 5 5 Table 2 Experimental results of Examples 1 to 7 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Adhesion level Level 0 Level 0 Level 0 Level 0 Level 0 Level 1 Viscosity is too high hardness 3H 5H 5H 3H 4H 6H Viscosity is too high Wear resistance Class B Level A Level A Level A Level A Level A Viscosity is too high Contact angle (degrees) 93.4 96.9 102.3 87.9 100.6 103.4 Viscosity is too high UV blocking rate (%) 91.36 91.35 91.68 91.66 91.28 91.55 Viscosity is too high It can be seen from Examples 1 to 3 that when the polyurethane acrylate is fluorosilicone-modified polyurethane acrylate, the coating has higher hardness, wear resistance and hydrophobicity. It can be seen from Examples 3 to 7 that when the mass proportion of fluorosilicone-modified polyurethane acrylate is 25%, the coating has the best adhesion to the glass while maintaining good hardness, wear resistance and hydrophobicity.

[0062] Table 3 Composition and content data of Examples 8 to 14 Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Fluorosilicone modified polyurethane acrylate 25 25 25 25 25 25 25 Modified epoxy acrylate 0 0 28 15 20 30 35 Bisphenol A epoxy acrylate 0 28 0 0 0 0 0 Novolac epoxy acrylate 28 0 0 0 0 0 0 Hexamethoxymethyl melamine resin 26 26 26 26 26 26 26 UV monomer 10 10 10 23 18 8 3 Photoinitiator 1 1 1 1 1 1 1 Triazine UV absorbers 5 5 5 5 5 5 5 Crosslinking aid 5 5 5 5 5 5 5 Table 4 Experimental results of Examples 8 to 14 Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Adhesion level Level 4 Level 4 Level 0 Level 1 Level 1 Level 1 Viscosity is too high hardness 5H 5H 5H 2H 3H 5H Viscosity is too high Wear resistance Level A Level A Level A Class B Class B Level A Viscosity is too high Contact angle (degrees) 103.3 102.1 103.1 104.2 103.9 102.4 Viscosity is too high UV blocking rate (%) 91.46 91.33 91.56 91.28 91.11 91.32 Viscosity is too high It can be seen from Examples 8 to 10 that when modified epoxy acrylate is used, the coating has better adhesion to the glass. It can be seen from Examples 10 to 14 that when the mass proportion of modified epoxy acrylate is 28%, the coating has the best adhesion to the glass while maintaining good hardness, wear resistance and hydrophobicity.

[0063] Table 5 Composition and content data of Examples 15 to 21 Embodiment 15 Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Embodiment 20 Embodiment 21 Fluorosilicone modified polyurethane acrylate 25 25 25 25 25 25 25 Modified epoxy acrylate 28 28 28 28 28 28 28 Hexamethoxymethyl melamine resin 0 0 26 15 20 25 30 High iminomethyl etherified amino resin 0 26 0 0 0 0 0 Butyl ether amino resin 26 0 0 0 0 0 0 UV monomer 10 10 10 21 16 11 6 Photoinitiator 1 1 1 1 1 1 1 Triazine UV absorbers 5 5 5 5 5 5 5 Crosslinking aid 5 5 5 5 5 5 5 Table 6 Experimental results of Examples 15 to 21 Embodiment 15 Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Embodiment 20 Embodiment 21 Adhesion level Level 4 Level 4 Level 0 Level 1 Level 1 Level 0 Level 1 hardness 2H 5H 5H 3H 3H 4H 5H Wear resistance Class B Level A Level A Class B Class B Level A Level A Contact angle (degrees) 101.0 101.9 102.7 103.5 103.6 102.0 103.5 UV blocking rate (%) 91.23 91.07 91.37 91.69 91.18 91.34 91.58 It can be seen from Examples 15 to 17 that when the amino resin is hexamethoxymethyl melamine resin, the coating has better adhesion, wear resistance and higher hardness. It can be seen from Examples 17 to 21 that when the mass proportion of hexamethoxymethyl melamine resin is 26%, the coating has the best adhesion to the glass while maintaining good hardness, wear resistance and hydrophobic properties.

[0064] Table 7 Composition and content data of Examples 22 to 28 Embodiment 22 Embodiment 23 Embodiment 24 Embodiment 25 Embodiment 26 Embodiment 27 Embodiment 28 Fluorosilicone modified polyurethane acrylate 25 25 25 25 25 25 25 Modified epoxy acrylate 28 28 28 28 28 28 28 Hexamethoxymethyl melamine resin 26 26 26 26 26 26 26 UV monomer 10 10 10 12 8 6 4 Photoinitiator 1 1 1 1 1 1 1 Benzophenone-based UV absorbers 5 0 0 0 0 0 0 Benzotriazole UV absorbers 0 5 0 0 0 0 0 Triazine UV absorbers 0 0 5 3 7 9 11 Crosslinking aid 5 5 5 5 5 5 5 Table 8 Experimental results of Examples 22 to 28 Embodiment 22 Embodiment 23 Embodiment 24 Embodiment 25 Embodiment 26 Embodiment 27 Embodiment 28 Adhesion level Level 0 Level 0 Level 0 Level 0 Level 0 Unable to solidify Unable to solidify hardness 5H 5H 5H 5H 3H Unable to solidify Unable to solidify Wear resistance Level A Level A Level A Level A Class B Unable to solidify Unable to solidify Contact angle (degrees) 102.8 102.9 104.7 103.7 102.8 Unable to solidify Unable to solidify UV blocking rate (%) 75.33 73.63 91.44 86.65 93.32 Unable to solidify Unable to solidify It can be seen from Examples 22 to 28 that when the triazine-based ultraviolet absorber is used as the ultraviolet light absorber, the ultraviolet light blocking rate reaches more than 90%. It can be seen from Examples 24 to 28 that when the mass proportion of the triazine-based ultraviolet light absorber is 5%, the ultraviolet light blocking rate of the coating is optimal and good hardness is maintained.

[0065] The above describes the main technical features and basic principles of the present invention and the related advantages. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the concept or basic features of the present invention. Therefore, no matter from which point of view, the above specific embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention.

[0066] In addition, it should be understood that although the present specification is described according to various implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation method may also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

Claims

1. A coating with high UV blocking rate, high hardness and high hydrophobicity, characterized in that: The composition is as follows: Polyurethane acrylate 20% to 35%; Epoxy acrylate 20% to 35%; Amino resin 20% to 35%; UV monomer 5%~15%; Photoinitiator 1% to 5%; Ultraviolet absorber 1% to 10%; Cross-linking agent 1%~10%.

2. A high ultraviolet blocking rate, high hardness and high hydrophobicity coating according to claim 1, characterized in that: The mass ratio of polyurethane acrylate, epoxy acrylate, amino resin and ultraviolet absorber is 25%:28%:26%:5%.

3. A high ultraviolet blocking rate, high hardness and high hydrophobicity coating according to claim 1, characterized in that: The mass ratio of UV monomer, photoinitiator and cross-linking aid is 10%:1%:5%.

4. A high ultraviolet blocking rate, high hardness and high hydrophobicity coating according to claim 1, characterized in that: The polyurethane acrylate is at least one of organic silicon modified polyurethane acrylate, organic fluorine modified polyurethane acrylate and fluorine silicon modified polyurethane acrylate; The epoxy acrylate is at least one of modified epoxy acrylate, bisphenol A epoxy acrylate, and novolac epoxy acrylate; The amino resin is at least one of hexamethoxymethyl melamine resin, high iminomethyl etherified amino resin, and butyl etherified amino resin; The ultraviolet absorber is at least one of a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber, and a triazine ultraviolet absorber.

5. The high ultraviolet blocking rate, high hardness and high hydrophobicity coating according to claim 1, characterized in that: The UV monomer is at least one of tris(2-hydroxyethyl)isocyanurate triacrylate, isobornyl methacrylate, and hydroxyethyl methacrylate; The photoinitiator is at least one of 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; The cross-linking aid is at least one of titanate, alkenyl silane coupling agent and amino silane coupling agent.

6. A high ultraviolet blocking rate, high hardness and high hydrophobicity coating according to claim 4, characterized in that: The polyurethane acrylate is fluorosilicone modified polyurethane acrylate; Epoxy acrylate is modified epoxy acrylate; The amino resin is hexamethoxymethyl melamine resin; The ultraviolet absorber is a triazine-based ultraviolet absorber.

7. The high ultraviolet blocking rate, high hardness and high hydrophobicity coating according to claim 5, characterized in that: The UV monomer is hydroxyethyl methacrylate; The photoinitiators are 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; The cross-linking aid is an aminosilane coupling agent.

8. The high ultraviolet blocking rate, high hardness and high hydrophobicity coating according to claim 7, characterized in that: The mass ratio of 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide to phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide is 8:

2.

9. The method for preparing a coating having high ultraviolet blocking rate, high hardness and high hydrophobicity according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Place polyurethane acrylate, epoxy acrylate, amino resin, UV monomer, and photoinitiator in a container, and mix and stir for 60 to 90 minutes to obtain a uniform mixture; (2) adding an ultraviolet absorber and a crosslinking aid to the mixture of step (1), mixing and stirring for 30 to 60 minutes to obtain a coating with high ultraviolet blocking rate, high hardness and high hydrophobicity; (3) Apply the coating of step (2) to the surface of the substrate with an ink knife, cover it with a layer of release film, roll it evenly, irradiate it with ultraviolet light, then remove the release film, and bake the substrate in a constant temperature oven at 150° C. for 30 min to 50 min to obtain a coating with high ultraviolet blocking rate, high hardness and high hydrophobicity.

10. The method for preparing a coating with high ultraviolet blocking rate, high hardness and high hydrophobicity according to claim 9, characterized in that: In step (3), the substrate is one of 1mm tempered glass, 3mm tempered glass, 1mm ultra-clear glass, and 3mm ultra-clear glass; the release film is a high-temperature resistant PET release film; the wet film thickness of the coating after rolling is uniformly applied is 10um to 20um; the ultraviolet light source is a 395nm-UVLED light source, and the amount of ultraviolet light is 1500mJ / cm 2 ~2000mJ / cm 2 .

Citation Information

Patent Citations

  • UV-cured high-wear-resistance and high-hydrophobicity coating and preparation method thereof

    CN115403969A

  • Thermosetting water ultraviolet isolating paint and coating therefrom

    CN1958698A

  • Ultraviolet curing anti-fingerprint coating for acrylic and composite material base material thereof

    CN103073934A

  • UV-curable coating

    CN103627312A

  • Preparation of epoxy resin modified polyurethane-acrylate photopolymerisable oligomer

    CN104448212A